Attention and awareness each influence amygdala activity for dynamic bodily expressions—a short review - De Gelder, Beatrice; Hortensius, Ruud; Tamietto, Marco (Frontiers in Integrative Neuroscience, 2012)
The amygdala (AMG) has long been viewed as the gateway to sensory processing of emotions and is also known to play an importanta role at the interface between cognition and emotion. However, the debate continues on whether AMG activation is independent of attentional demands. Recently, researchers started exploring AMG functions using dynamic stimuli rather than the traditional pictures of facial expressions. Our present goal is to review some recent studies using dynamic stimuli to investigate AMG activation and discuss the impact of different viewing conditions, including oddball detection, explicit or implicit recognition, variable cognitive task load, and non-conscious perception. In the second part we relate these different effects to a dynamic dual route model of affective processing and discuss its implications for AMG activity. We sketch a dynamic dual route perspective of affective perception and we argue that this allows for multiple AMG involvement in separate networks and at different times in the processing streams. Attention has a different impact on these separate but interacting networks. Route I is engaged in early emotion processing, is partly supported by AMG activity and is possibly independent of attention, whereas activity in the later emotion processing is influenced by attention. Route II is a cortical-based network that underlies body recognition and action representation. The end result of route I and II is reflexive and voluntary behavior respectively. We conclude that using dynamic emotion stimuli and a dynamic dual route model of affective perception can provide new insights into the varieties of AMG activation.